2013
DOI: 10.4103/0259-1162.118950
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine: Anesthetic consideration in elderly patients for transurethral resection of prostrate a clinical trial

Abstract: Background:Ropivacaine has less systemic toxicity and greater differentiation of sensory and motor blockade after subarachnoid block. This study was aimed to evaluate the anesthetic efficacy of intrathecal 0.75% isobaric ropivacaine alone or with fentanyl in elderly patients undergoing transurethral resection of prostrate.Materials and Methods:Fifty four elderly consented patients of ASA grade I-III scheduled for transurethral resection of prostrate under the subarachnoid block were randomized to receive eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 14 publications
4
9
0
Order By: Relevance
“…In contrast to our study, other studies comparing Ropivacaine versus Ropivacaine plus Fentanyl, there was no significant difference in sensory onset in two groups. 9,10,16,17 It could be attributed to two factors, firstly, in study by Gupta et al 16 and Seetharam et al 17 normal saline was added in 'Ropivacaine only' Group to make equal volume as in 'Ropivacaine + Fentanyl' Group. Intrathecal solution in both Groups thus became hypobaric and similar sensory onset was observed.…”
Section: Observations and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to our study, other studies comparing Ropivacaine versus Ropivacaine plus Fentanyl, there was no significant difference in sensory onset in two groups. 9,10,16,17 It could be attributed to two factors, firstly, in study by Gupta et al 16 and Seetharam et al 17 normal saline was added in 'Ropivacaine only' Group to make equal volume as in 'Ropivacaine + Fentanyl' Group. Intrathecal solution in both Groups thus became hypobaric and similar sensory onset was observed.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…Ropivacaine has been successfully used in spinal anaesthesia for caesarean section, nephrotic surgery and orthopaedic surgery of lower extremity. [8][9][10][11][12] However there is scarcity of data in which ropivacaine has been used in SAB for vaginal hysterectomy in which there is more extensive surgery, needing more relaxation than above mentioned surgeries. 13 This prompted us to plan present study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent clinical data have shown that ropivacaine is clinically effective and safe for regional anaesthetic techniques with good tolerability. 2 Ropivacaine could provide adequate surgical anaesthesia without compromising early ambulation and discharge. 2 Corticosteroids have been studied recently as adjuncts to local anaesthetics in regional block.…”
mentioning
confidence: 99%
“…2 Ropivacaine could provide adequate surgical anaesthesia without compromising early ambulation and discharge. 2 Corticosteroids have been studied recently as adjuncts to local anaesthetics in regional block. 3 Ropivacaine is less lipophilic than bupivacaine and is associated with decreased potential for central nervous system toxicity and cardiotoxicity.…”
mentioning
confidence: 99%